Association between social determinants and neurocognitive disorders among older adults in Peru - Runzer Colmenares, Fernando Miguel (2026)
Objective: To determine the association between social determinants and neurocognitive disorders among older adults from Centro Médico Naval (CEMENA) in Callao and high-Andean communities in Peru. Materials and methods: An analytical observational study was conducted based on a secondary analysis of two databases: CEMENA Frailty Study and ANDES Frail. Adultsaged ≥ 60 years were included. Cognitive impairment was assessed using Pfeiffer’s questionnaire (SPMSQ). Social determinants included variables such as social and family support, comorbidities, educational level, self-perceived social support, access to hospital and emergency services, and geographic location. Bivariate and multivariate analyses were performed using Poisson regression to estimate prevalence ratios (PRs) and their 95% confidence intervals (95% CIs). A p value < 0.05 was considered statistically significant. Analyses were adjusted for relevant sociodemographic variables. Results: A total of 2,086 participants were analyzed. Cognitive impairment was significantly associated with several social and health determinants. Factors associated with cognitive impairment included poor social and family environment (PR = 6.95), residence in coastal areas (PR = 1.60), having two or more comorbidities (PR = 1.86), and having ≤ 11 years of education (PR = 1.59). Male sex was also identified as a risk factor (PR = 2.12). These findings highlight the influence of social determinants on cognitive impairment and suggest that vulnerability to these factors substantially contributes to the development of this condition. Conclusions: The results reinforcethe influence of social and health determinants on cognitive impairment among older adults. They emphasize the need to implement comprehensive interventions addressing both clinical and social factors. Such an approach could improve the early detection, prevention, and management of cognitive impairment in vulnerable populations, while also informing public policies aimed at reducing health inequities.